Fasting in the Perspective of Buddhism - Lisniasari Lisniasari; Tejo Ismoyo; Alika Setia Putri; Dharma Nata Saputra; Duta Nyana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to examine fasting from a Buddhist perspective. This research is a qualitative research using the literature method to find out how fasting is carried out by Buddhists. The results of the study show that fasting in Buddhism is an attempt to avoid taking food or drink at the wrong time, which is known as Uposatha. Fasting for Buddhists falls on the 1st, 8th, 15th and 23rd. So for Buddhists who want to fast, they must observe the eight precepts, namely: not killing living beings of any kind, not stealing, not having sex, not lying, do not drink intoxicating drinks, do not eat after the appointed time, do not beautify themselves and do not be extravagant. Fasting in Buddhism is not obligatory for its adherents. However, if Buddhists wish and intend to observe the uposatha (fasting) it is permissible. Thus, fasting in Buddhism aims not only to control oneself from eating and drinking, but includes all movements of the mind, speech, and body.